Co-Exposure of Cardiomyocytes to IFN-γ and TNF-α Induces Mitochondrial Dysfunction and Nitro-Oxidative Stress: Implications for the Pathogenesis of Chronic Chagas Disease Cardiomyopathy - Nunes, João Paulo Silva; Andrieux, Pauline; Brochet, Pauline; Almeida, Rafael Ribeiro; Kitano, Eduardo; Honda, André Kenji; Iwai, Leo Kei; Andrade-Silva, Débora; Goudenège, David; Alcântara Silva, Karla Deysiree; Vieira, Raquel de Souza; Levy, Débora; et al. (Frontiers in Immunology, 2021)
Infection by the protozoan Trypanosoma cruzi causes Chagas disease cardiomyopathy (CCC) and can lead to arrhythmia, heart failure and death. Chagas disease affects 8 million people worldwide, and chronic production of the cytokines IFN-γ and TNF-α by T cells together with mitochondrial dysfunction are important players for the poor prognosis of the disease. Mitochondria occupy 40% of the cardiomyocytes volume and produce 95% of cellular ATP that sustain the life-long cycles of heart contraction. As IFN-γ and TNF-α have been described to affect mitochondrial function, we hypothesized that IFN-γ and TNF-α are involved in the myocardial mitochondrial dysfunction observed in CCC patients. In this study, we quantified markers of mitochondrial dysfunction and nitro-oxidative stress in CCC heart tissue and in IFN-γ/TNF-α-stimulated AC-16 human cardiomyocytes. We found that CCC myocardium displayed increased levels of nitro-oxidative stress and reduced mitochondrial DNA as compared with myocardial tissue from patients with dilated cardiomyopathy (DCM). IFN-γ/TNF-α treatment of AC-16 cardiomyocytes induced increased nitro-oxidative stress and decreased the mitochondrial membrane potential (ΔΨm). We found that the STAT1/NF-κB/NOS2 axis is involved in the IFN-γ/TNF-α-induced decrease of ΔΨm in AC-16 cardiomyocytes. Furthermore, treatment with mitochondria-sparing agonists of AMPK, NRF2 and SIRT1 rescues ΔΨm in IFN-γ/TNF-α-stimulated cells. Proteomic and gene expression analyses revealed that IFN-γ/TNF-α-treated cells corroborate mitochondrial dysfunction, transmembrane potential of mitochondria, altered fatty acid metabolism and cardiac necrosis/cell death. Functional assays conducted on Seahorse respirometer showed that cytokine-stimulated cells display decreased glycolytic and mitochondrial ATP production, dependency of fatty acid oxidation as well as increased proton leak and non-mitochondrial oxygen consumption. Together, our results suggest that IFN-γ and TNF-α cause direct damage to cardiomyocytes’ mitochondria by promoting oxidative and nitrosative stress and impairing energy production pathways. We hypothesize that treatment with agonists of AMPK, NRF2 and SIRT1 might be an approach to ameliorate the progression of Chagas disease cardiomyopathy.